Hyperoxia and Lungs: What We Have Learned From Animal Models - Amarelle, Luciano; Quintela, Lucía; Hurtado, Javier; Malacrida, Leonel (Frontiers in Medicine, 2021)
Although oxygen (O2) is essential for aerobic life, it can also be an important source of cellular damage. Supra-physiological levels of O2 determine toxicity due to exacerbated reactive oxygen species (ROS) production, impairing the homeostatic balance of several cellular processes. Furthermore, injured cells activate inflammation cascades, amplifying the tissue damage. The lung is the first (but not the only) organ affected by this condition. Critically ill patients are often exposed to several insults, such as mechanical ventilation, infections, hypo-perfusion, systemic inflammation, and drug toxicity. In this scenario, it is not easy to dissect the effect of oxygen toxicity. Translational investigations with animal models are essential to explore injuring stimuli in controlled experimental conditions, and are milestones in understanding pathological mechanisms and developing therapeutic strategies. Animal models can resemble what happens in critical care or anesthesia patients under mechanical ventilation and hyperoxia, but are also critical to explore the effect of O2 on lung development and the role of hyperoxic damage on bronchopulmonary dysplasia. Here, we set out to review the hyperoxia effects on lung pathology, contributing to the field by describing and analyzing animal experimentation's main aspects and its implications on human lung diseases.